The Efficacy of a Multimodal Pedagogical Interventions on ESP Vocabulary Mastery among Civic Education Students - Adys, Himala Praptami; Amin, Fatimah Hidayahni; Sakkir, Geminastiti (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2026)
This study examines the effectiveness of multimodal instructional media integrating text-based and video-based materials in developing English for Specific Purposes (ESP) vocabulary among Civic Education students, while also investigating potential gender-related differences in learning outcomes. Anchored in multimodal learning theory, the study proceeds from the premise that text and video constitute complementary rather than competing modes of vocabulary instruction, each contributing unique affordances to learners' lexical development. An interrupted time series quasi-experimental design was adopted, involving 82 second-semester Civic Education students at Universitas Negeri Makassar, Indonesia, who participated in four structured treatment sessions alternating between text-based and video-based instruction. Pre-test and post-test assessments were administered at every session, consistently demonstrating significant vocabulary gains across all treatments. Mean scores progressed from 75 (pre-test, Session 1) to 88 (post-test, Session 4), with female students outperforming their male counterparts across all assessment points. These findings contribute substantively to the ESP vocabulary research literature by demonstrating that multimodal text-video integration yields both immediate and cumulative vocabulary gains, and by foregrounding the pedagogical significance of gender as a variable in ESP instructional design.